Association between celiac disease and schizophrenia: a meta-analysis. Issue 4 (April 2018) - Wijarnpreecha, Karn; Jaruvongvanich, Veeravich; Cheungpasitporn, Wisit; Ungprasert, Patompong
Abstract : Background/objective: Recent epidemiologic studies have suggested that patients with celiac disease might be at an increased risk of schizophrenia. However, the data on this risk remain inconclusive. This meta-analysis was conducted with the aim to summarize all available evidence. Methods: A literature search was carried out using MEDLINE and Embase database from inception to June 2017. Studies that compared the risk of schizophrenia among patients with celiac disease versus individuals without celiac disease were included. Pooled odds ratio and 95% confidence interval were calculated using a random-effect, generic inverse-variance method. Results: Of the 284 retrieved studies, four met our eligibility criteria and were included in the analysis. We found a higher risk of schizophrenia among patients with celiac disease compared with individuals without celiac disease with the pooled odds ratio of 2.03 (95% confidence interval: 1.45–2.86). The statistical heterogeneity of this study was insignificant ( I 2 =0%). Conclusion: This systematic review and meta-analysis found a significantly higher risk of schizophrenia among patients with celiac disease. Abstract : Supplemental Digital Content is available in the text.